Mapeamento dos mercados e canais de comercialização da APOFAC de Humaitá/AM - Relvas, Carlos Henrique Gima (Brasil, 2022)
Studies focused on agricultural market allow an understanding of how famiy farming can have access to income Generation, more than that, gives opportunity to understand the difficulties faced by family farmers for rural development, especially in the socioeconomic and social reproduction aspects. The Markets are fundamental for productive inclusion and are built from the interaction of family farmers in the commercialization channels APOFAC is the Association of Producers of Horti-Fruti Farmers of Alto Crato, which was created in order to organize a group of farmers strengthening family production, contributing to the economic development of these producers. Inside of the association are found activities such as animal husbandry, cattle (beef/milk) pigs and fish, in addition to Hortifruti production. With this diversity of products, it is possible to have access to different commercialization channels, consequently different markets. Therefore, this work objective to analyze the markets and the the marketing channels accessed by members of the Association of Producers of Hortifrutigranjeiros do Alto Crato – APOFAC The methodology used to map markets and sales channels is qualitative in nature, being exploratory, descriptive and explanatory methods, to conduct the classification, the typology proposed by s was used.by Schneider (2016), which addresses four types of markets, proximity, territorial, conventional and institutional. In this work, several commercialization channels were found, such as fairs, supermarkets, middleman, sale on the property, sale with home deliveries and sales to public bodies. Each marketing channel is part of a type of market, so that the four markets proposed in the methodology were found. Finally, it was found that there is a diversity of means to access markets, but there is still misinformation and lack of incentives on the part of government organizations, especially technical assistance and infrastructure to sell products.